A type of self-healable, dissoluble and stretchable organosilicon elastomer for flexible electronic devices. (5th July 2020) - Zhang, Kaiming; Liu, Yuetao; Wang, Zhe; Song, Chengxin; Gao, Chuanhui; Wu, Yumin
Graphical abstract: Highlights: As the synergistic effect of the imine bond the boron oxygen bonds and hydrogen bonds, the network could be self-healed at room temperature or high temperature or in water. Using PDMS with low molecular weight, the polymer has more crosslinking sites. The elastomer has excellent mechanical properties, fatigue resistance and stability. PDMS elastomer can be rapidly dissolved by amino or methylamino reagents. The self-healing conductive material is very sensitive to deformation and has a great prospect in sensor field. Abstract: Polymer materials with good mechanical properties, solubility and flexible self-healing conditions were of great value to the development of modern high-tech fields. Herein, α, ω-aminopropyl terminated polydimethylsiloxane (PDMS, Mn = 2000), terephthalaldehyd (TA) and 3-aminophenylboronic acid (APB) were used to construct a three-dimensional network via simple and effective reactions, such as the Schiff base reaction and the dehydration reaction. The obtained PDMS elastomer prepared by low molecular weight main chain could achieve very good mechanical performance of tensile strength 2.54 MPa and the average elongation at break of 275.3%. Through the dynamic imine bonds formed by Schiff base reaction and the coordination of boron oxygen bonds and hydrogen bonds, we have constructed a high efficiency self-healing network. The network could achieve self-healing at room temperature with a self-healing efficiency of 91.6%, at high temperature with a self-healing efficiency of 95.1% and in water at a self-healing efficiency of 85.5%. In addition, multi-walled carbon nanotubes (MWCNTs) was compounded with a polymer system to prepare self-healing flexible electronic devices. Due to the electric resistance of PDMS/MWCNTs sensitively modified with the change of tensile and bending angles, this might be of great significance for the application of sensors.